Prevalence of Maxillary Permanent Canine Impaction in Relation to Anomalous Lateral Incisors - İlknur Veli; Burçin Yüksel; Tancan Uysal (Galenos Yayinevi, 2014)
Objective:The aim of this study was to document the prevalence of maxillary permanent canine impaction in relation to anomalous adjacent lateral incisors in a Turkish population.Materials and MethodsPretreatment orthodontic records of 68 subjects (27 male, 41 female) with palatal or buccal impaction of one or both permanent maxillary canines were included in this study. Localization of the impacted permanent canines was determined by using cone-beam computed tomography images and classified as buccal or palatal impaction. Maxillary lateral incisors were recorded as normal, small, peg shaped, impacted, or missing using 3-dimensional digital models. The percentage of the total sample in each group was calculated, and the significance of the relationship between canine impaction and anomalous lateral incisors was examined with the Pearson v2 test at a significance level of 0.05.Results:The overall prevalence of peg-shaped maxillary permanent lateral incisors was found to be 18.3%. Impaction of the maxillary canine was 5.18 times more common in females than males, and palatal canine impaction was almost 1.27 times more common than the buccal impaction.Conclusion:Palatally impacted maxillary permanent canines were more common than buccally impacted canines and occurred more often in female subjects. Also, the prevalence of maxillary canine impaction in association with anomalous lateral incisors was different among Turkish males and females.